Arabidopsis HFR1 is a potential nuclear substrate regulated by the Xanthomonas type III effector XopD(Xcc8004). - Choon Meng Tan; Meng-Ying Li; Pei-Yun Yang; Shu Heng Chang; Yi-Ping Ho; Hong Lin; Wen-Ling Deng; Jun-Yi Yang (PLoS ONE)
XopDXcc8004, a type III effector of Xanthomonas campestris pv. campestris (Xcc) 8004, is considered a shorter version of the XopD, which lacks the N-terminal domain. To understand the functions of XopDXcc8004, in planta, a transgenic approach combined with inducible promoter to analyze the effects of XopDXcc8004 in Arabidopsis was done. Here, the expression of XopDXcc8004, in Arabidopsis elicited the accumulation of host defense-response genes. These molecular changes were dependent on salicylic acid and correlated with lesion-mimic phenotypes observed in XVE::XopDXcc8004 transgenic plants. Moreover, XopDXcc8004 was able to desumoylate HFR1, a basic helix-loop-helix transcription factor involved in photomorphogenesis, through SUMO protease activity. Interestingly, the hfr1-201 mutant increased the expression of host defense-response genes and displayed a resistance phenotype to Xcc8004. These data suggest that HFR1 is involved in plant innate immunity and is potentially regulated by XopDXcc8004.